Influenza surveillance capacity improvements in Africa during 2011‐2017. Issue 4 (4th November 2020) - Igboh, Ledor S.; McMorrow, Meredith; Tempia, Stefano; Emukule, Gideon O.; Talla Nzussouo, Ndahwouh; McCarron, Margaret; Williams, Thelma; Weatherspoon, Vashonia; Moen, Ann; Fawzi, Derrar; Njouom, Richard; Nakoune, Emmanuel; et al.
Abstract: Background: Influenza surveillance helps time prevention and control interventions especially where complex seasonal patterns exist. We assessed influenza surveillance sustainability in Africa where influenza activity varies and external funds for surveillance have decreased. Methods: We surveyed African Network for Influenza Surveillance and Epidemiology ( ANISE) countries about 2011‐2017 surveillance system characteristics. Data were summarized with descriptive statistics and analyzed with univariate and multivariable analyses to quantify sustained or expanded influenza surveillance capacity in Africa. Results: Eighteen (75%) of 24 ANISE members participated in the survey; their cumulative population of 710 751 471 represent 56% of Africa's total population. All 18 countries scored a mean 95% on WHO laboratory quality assurance panels. The number of samples collected from severe acute respiratory infection case‐patients remained consistent between 2011 and 2017 (13 823 vs 13 674 respectively) but decreased by 12% for influenza‐like illness case‐patients (16 210 vs 14 477). Nine (50%) gained capacity to lineage‐type influenza B. The number of countries reporting each week to WHO FluNet increased from 15 (83%) in 2011 to 17 (94%) in 2017. Conclusions: Despite declines in external surveillance funding, ANISE countries gained additional laboratory testing capacity and continued influenza testing and reporting to WHO. These gains represent important achievements toward sustainable surveillance and epidemic/pandemic preparedness.